## College Algebra (6th Edition)

The solutions are $x=\dfrac{5}{6}\pm\dfrac{\sqrt{145}}{6}$
$3x^{2}-5x-10=0$ Take out common factor $3$ from the left side of the equation: $3\Big(x^{2}-\dfrac{5}{3}x-\dfrac{10}{3}\Big)=0$ Take the $3$ to divide the right side: $x^{2}-\dfrac{5}{3}x-\dfrac{10}{3}=\dfrac{0}{3}$ $x^{2}-\dfrac{5}{3}x-\dfrac{10}{3}=0$ Take $\dfrac{10}{3}$ to the right side: $x^{2}-\dfrac{5}{3}x=\dfrac{10}{3}$ Add $\Big(\dfrac{b}{2}\Big)^{2}$ to both sides of the equation. In this case, $b=-\dfrac{5}{3}$ $x^{2}-\dfrac{5}{3}x+\Big(-\dfrac{5}{3\cdot2}\Big)^{2}=\dfrac{10}{3}+\Big(-\dfrac{5}{3\cdot2}\Big)^{2}$ $x^{2}-\dfrac{5}{3}x+\dfrac{25}{36}=\dfrac{10}{3}+\dfrac{25}{36}$ $x^{2}-\dfrac{5}{3}x+\dfrac{25}{36}=\dfrac{145}{36}$ Factor the left side of the equation, which is a perfect square trinomial: $\Big(x-\dfrac{5}{6}\Big)^{2}=\dfrac{145}{36}$ Take the square root of both sides: $\sqrt{\Big(x-\dfrac{5}{6}\Big)^{2}}=\pm\sqrt{\dfrac{145}{36}}$ $x-\dfrac{5}{6}=\pm\dfrac{\sqrt{145}}{6}$ Solve for $x$: $x=\dfrac{5}{6}\pm\dfrac{\sqrt{145}}{6}$